Development and Validation of Manipulatives in Teaching Mathematics 6 - Turro, Ian Rey K.; Giducos, Romeo M (RIRAI Publisher, 2025)
This study focused on the development and validation of manipulatives as strategic intervention materials for teaching Mathematics 6 at Manapa I Elementary School. Grounded in the Constructivist Learning Theory, the research aimed to enhance learners’ conceptual understanding by addressing their least-learned competencies through interactive learning tools. A descriptive-developmental research design was employed, involving the identification of learning gaps, creation of manipulatives, expert validation, and classroom implementation. The study identified key mathematical challenges among Grade 6 learners, particularly in differentiating expressions from equations. Manipulatives were designed to bridge these gaps by providing concrete representations of abstract concepts, fostering critical thinking and problem-solving skills. Experts evaluated the manipulatives based on content, format, presentation, organization, accuracy, and durability, confirming their suitability for instructional use. Findings revealed a significant improvement in learners’ mathematical performance, with post-test scores demonstrating increased mastery levels compared to pretest assessments. The study highlights the effectiveness of manipulatives in promoting engagement, reinforcing conceptual understanding, and supporting struggling learners in mathematics. It contributes to the growing discourse on manipulative-based learning strategies, emphasizing the importance of integrating interactive materials into mathematics education to enhance student learning outcomes.